PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE PEMBERIAN LATIHAN PRAKTEK MANDIRI TERBIMBING PADA MATA PELAJARAN INSTALASI PENERANGAN LISTRIK DI KELAS XI TITL 1 SMK NEGERI 1 MANDAU SEMESTER 1 TAHUN PELAJARAN 2019 / 2020 - Syaiful Desra (Ensiklopedia of Journal, 2022)
This research begins with students who cannot do practical job sheets and only copy and copy their friends' work, the authors see that students need guidance / direction so that they are willing to work and be active in PHB assembly practice activities and are able to complete practical job sheets. well and perfectly. The research that the writer did was Classroom Action Research (CAR). The subjects in this action research were students of Class XI Electrical Power Installation Engineering (TITL 1) at SMK Negeri 1 Mandau with 11 students. The data collection technique used in this research is a series of photo folio assessments to evaluate the quality and quantity of the self-guided training method carried out by researchers collaborating with an observer. Data analysis was carried out qualitatively. Based on the results of observations and student learning outcomes in each cycle, it is known that: (1) Providing Guided Independent Practice Exercises is proven to improve student learning outcomes in the subject of Electrical Lighting Installation in Class XI TITL SMK Negeri 1 Mandau, amounting to 96.29% (2) Carrying out practical competency exams (UKP) with not too many test materials can spur students to get good grades of 96%. It can be concluded that the implementation of research using learning with this training method can improve learning outcomes.Keywords: Method of Giving Guided Independent Practice Exercises, Electrical Lighting Installation Subjects.